Conformational Dynamics and Stability of HP35 Studied with 2D IR Vibrational Echoes - Chung, Jean K. (2012)
Two-dimensional infrared (2D IR) vibrational echo spectroscopy was used to measure the fast dynamics of two variants of chicken villin headpiece 35 (HP35) using the CN of cyanophenylalanine residues inserted in the hydrophobic core as a vibrational probe. Experiments were performed on both singly (HP35-P) and doubly CN-labeled peptide (HP35-P(2)) within the wild-type sequence, as well as on HP-35 containing a singly labeled cyanophenylalanine and two norleucine mutations (HP35-P NleNle). There is a remarkable similarity between the dynamics measured in singly and doubly CN labeled HP35, demonstrating that the presence of an additional CN vibrational probe does not significantly alter the dynamics of the small peptide. The substitution of two lysine residues by norleucines markedly improves the stability of HP35 by replacing charged with nonpolar residues, stabilizing the hydrophobic core. The results of the 2D IR experiments reveal that the dynamics of HP35-P are significantly faster than HP35-P NleNle. These observations suggest that the slower structural fluctuations in the hydrophobic core, indicating a more tightly structured core, may be an important contributing factor to HP35-P NleNle’s increased stability.